2019
DOI: 10.1038/s41598-019-52985-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circulating Serum Multi-MicroRNA Signatures in Human DLBCL Models

Abstract: There remains a need to identify new sensitive diagnostic and predictive blood-based platforms in lymphoma. We previously discovered a novel circulating microRNA (miRNA) signature in a Smurf2-deficient mouse model that spontaneously develops diffuse large B-cell lymphoma (DLBCL). Herein, we investigated this 10-miRNA signature (miR-15a, let-7c, let-7b, miR-27a, miR-10b, miR-18a, miR-497, miR-130a, miR24, and miR-155) in human lymphoma cell lines, mice engrafted with patient-derived xenografts (PDXs), and DLBCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Due to their important role in gene expression regulation ( O'Brien et al., 2018 ), contribution to immunity ( Tsitsiou and Lindsay, 2009 ), and importance for therapeutic purposes ( van Rooij and Kauppinen, 2014 ), we sought to assess the circulating miRNA profile expressed in the plasma following simulated deep space exposures. We focused on miRNAs in plasma, as we have demonstrated that the immune system dysregulation is systemic and circulating ( Beheshti et al., 2017 , 2018 , 2019 ; Mehta and Baltimore, 2016 ; Montagner et al., 2013 ; Schwarzenbach and Gahan, 2019 ). To determine the overall impact that miRNAs have on the immune system, we first predicted gene ontology (GO) terms with an false discovery rate < 0.05 from processed miRNA-sequenced plasma data for all conditions and filtered for specific immune GO terms ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to their important role in gene expression regulation ( O'Brien et al., 2018 ), contribution to immunity ( Tsitsiou and Lindsay, 2009 ), and importance for therapeutic purposes ( van Rooij and Kauppinen, 2014 ), we sought to assess the circulating miRNA profile expressed in the plasma following simulated deep space exposures. We focused on miRNAs in plasma, as we have demonstrated that the immune system dysregulation is systemic and circulating ( Beheshti et al., 2017 , 2018 , 2019 ; Mehta and Baltimore, 2016 ; Montagner et al., 2013 ; Schwarzenbach and Gahan, 2019 ). To determine the overall impact that miRNAs have on the immune system, we first predicted gene ontology (GO) terms with an false discovery rate < 0.05 from processed miRNA-sequenced plasma data for all conditions and filtered for specific immune GO terms ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The synergistic effect of heavy and light ions together is a highly complex response that requires control by key regulators. We have previously identified and validated a spaceflight signature of circulating miRNAs associated with cardiovascular damage ( Beheshti et al., 2018 , 2019 ; Malkani et al., 2020 ). We have also shown that these circulating miRNAs can be systemic drivers in the host to promote increased health risks due to heavy and light ion exposure ( Malkani et al., 2020 ; Paul et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously identified and validated a spaceflight signature of three specific miRNAs associated with cardiovascular damage: these are let-7a-5p, miR-125b-5p, and miR-16-5p ( Beheshti et al., 2018 , 2019 ; Malkani et al., 2020 ). We found that these miRNAs were upregulated in mature micro-vessels and validated as effectors of simGCRsim-induced micro-vessel collapse ( Malkani et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, pathways and processes associated to drug resistance were regulated as well by the miRNAs here found, such as the fatty acid biosynthesis and metabolism. Fatty acid receptor GPCR120, has been described as responsible to up-regulate ABC transporters and trigger chemoresistance in breast cancer [ 29 ], and the fatty acid synthase was reported to be involved in DLBCL progression [ 30 ]. In addition, the neurotrophin TRK receptor signaling has also found to be regulated by these miRNAs, being associated to a more aggressive DLBCL phenotype, rituximab-resistance and pro-survival response to chemotherapeutic agents [ [31] , [32] , [33] , [34] , [35] ].…”
Section: Discussionmentioning
confidence: 99%